2004
DOI: 10.1002/hyp.5560
|View full text |Cite
|
Sign up to set email alerts
|

The influences of the Southern and North Atlantic Oscillations on climatic surface variables in Turkey

Abstract: Abstract:In this study, Turkish climatic variables (precipitation, stream flow and maximum and minimum temperatures) were first analysed in association with both the Southern Oscillation (SO) and the North Atlantic Oscillation (NAO). The relationships between Turkish maximum and minimum monthly temperatures and the extreme phases of the SO (El Niño and La Niña events) were examined. The results of this analysis showed that relationships between Turkish monthly maximum temperatures and El Niño and La Niña conta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
54
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
8
1
1

Relationship

3
7

Authors

Journals

citations
Cited by 80 publications
(57 citation statements)
references
References 29 publications
2
54
1
Order By: Relevance
“…In the Mediterranean area, a correlation between the NAO, precipitation, river discharges and lake levels was also found in the Middle East and in Turkey (Cullen and deMenocal, 2000;Cullen et al, 2002;Karabörk et al, 2005;Türkes and Erlat, 2005;Kücük et al, 2009). A strong interdependence among the NAO, precipitation, river discharges and air temperature in some southern Italy regions (Brandimarte et al, 2011;Caloiero et al, 2011) was discovered.…”
Section: Introductionmentioning
confidence: 92%
“…In the Mediterranean area, a correlation between the NAO, precipitation, river discharges and lake levels was also found in the Middle East and in Turkey (Cullen and deMenocal, 2000;Cullen et al, 2002;Karabörk et al, 2005;Türkes and Erlat, 2005;Kücük et al, 2009). A strong interdependence among the NAO, precipitation, river discharges and air temperature in some southern Italy regions (Brandimarte et al, 2011;Caloiero et al, 2011) was discovered.…”
Section: Introductionmentioning
confidence: 92%
“…Previously, much work had focused on North American and European countries owing to the ready availability of abundant data. With the expansion of the global climatic datasets, a worldwide increase in the number of studies on climate variability has taken place, leading to a better understanding of the climate system (Jones and Mann 2004;Charlson and Wigley 1994;Kahya and Karabörk 2001;Kalaycı and Kahya 2006;Karabörk et al 2005;Karaca et al 1995Karaca et al , 2000Karl et al 1993;Kiehl et al 2000;Nasrallah and Balling 1993;Tayanç and Toros 1997;Tayanç et al , 1998aWigley 2005;Ezber et al 2006;WMO 1992).…”
Section: Introductionmentioning
confidence: 98%
“…In the Mediterranean region a negative relationship between the NAO and river discharges has been found in the Middle East (Cullen and DeMenocal, 2000;Cullen et al, 2002) and in Turkey (Karabörk et al, 2005;Kalayci and Kahya, 2006), where lake levels have also been related to the NAO (Kücük et al, 2009). Within the Iberian Peninsula (hereafter IP) the influence of the NAO on river discharges has been analyzed in studies of various basins (López-Moreno et al, 2007;Trigo et al, 2004;Morán-Tejeda et al, 2011), where reasonably high correlations have been found between the NAO and streamflows, particularly in winter.…”
Section: Introductionmentioning
confidence: 99%